En humanistisk fågel Fenix: Från kris till offensiv - Eklöf, Jenny; Nordlund, Christer (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2013)
The consolidation of the USSTE research group in Umeå grew out of two favorable conditions: the Faculty of Arts’ economic crisis which was turned into a window of opportunity and the ability by the existing USSTE researchers at the time to constitute a credible recipient of such support. The future for USSTE depends both on how well its researchers can continue to perform according to established quality criteria, but also if it can manage to consolidate a sense of its own expertise, its own version of relevance, and engage in an international conversation on contemporary societal challenges.